2008
DOI: 10.1016/j.expneurol.2008.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates early pyramidal neuron excitability impairment and death in acute rat hippocampal slices caused by oxygen-glucose deprivation

Abstract: Accumulating evidence indicates that the polyphenol resveratrol (trans-3, 5, 4′-trihydroxystibene, RVT) potently protects against cerebral ischemia neuronal damage due to its oxygen free radicals scavenging and antioxidant properties. However, it is unknown whether RVT can attenuate ischemiainduced early impairment of neuronal excitability. To address this question, we simulated ischemic conditions by applying oxygen-glucose deprivation (OGD) to acute rat hippocampal slices and examined the effect of RVT on OG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 36 publications
1
48
0
Order By: Relevance
“…Resveratrol (trans-3,4′,5-trihydroxystilbene), a unique phytoalexin widely distributed in natural plants, possesses a strong antioxidant activity capable of opposing the potentially cytotoxic stresses of oxidative damage [6]. Several in vitro studies have identified that resveratrol may protect various neuronal cell types from oxidative stress-induced cell death [7][8][9]. A previous in vivo research has suggested that dietary administration of resveratrol to elderly male Wistar rats confers protection against recurrent ischemic insult caused by two mild transient middle cerebral artery occlusions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (trans-3,4′,5-trihydroxystilbene), a unique phytoalexin widely distributed in natural plants, possesses a strong antioxidant activity capable of opposing the potentially cytotoxic stresses of oxidative damage [6]. Several in vitro studies have identified that resveratrol may protect various neuronal cell types from oxidative stress-induced cell death [7][8][9]. A previous in vivo research has suggested that dietary administration of resveratrol to elderly male Wistar rats confers protection against recurrent ischemic insult caused by two mild transient middle cerebral artery occlusions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Res also markedly reduced the amplitude and frequency of AMPA-mediated spontaneous excitatory postsynaptic currents in rat hippocampal pyramidal neurons [27]. Furthermore, trans-Res significantly suppressed Glu-induced currents in rat hippocampal postsynaptic CA1 pyramidal neurons, and NMDA and KA receptors were more sensitive than AMPA receptors to trans-Res [17].…”
Section: Res-mediated Neuroprotective Effect Against Glu-induced Excimentioning
confidence: 90%
“…The uncompetitive NMDA receptor antagonist memantine, is able to protect dissociated cortical neurons from Glu-induced excitotoxicity [26]. Res attenuates oxygen-glucose deprivationinduced neuron impairment and death in acute rat hippocampal slices by enhancing the activation of the large-conductance potassium channel and reducing the enhanced AMPA/NMDA receptor-mediated neuronal excitatory postsynaptic currents caused by oxygen-glucose deprivation [27]. Furthermore, some studies support that trans-Res inhibites the postsynaptic Glu receptors in hippocampal neurons, with NMDA receptors being more sensitive than AMPA receptors [17], which probably have an antioxidant effect that ameliorates ischemic brain injury.…”
Section: Res-mediated Neuroprotective Effects Against Glu-induced Excmentioning
confidence: 99%
“…Other studies have shown that resveratrol decreases the activity of the NMDA receptors and also the related kainate receptors, acting on both the receptor activities themselves [309][310][311] and also acting to increase glutamate transport [312], thus lowering the extracellular glutamate that acts as an NMDA agonist. In each of these actions, resveratrol is thought to act by stimulating the activity of SIRT1, a protein that has a wide ranging activity in regulating gene expression.…”
Section: Is Resveratrol a Magic Bullet For The Treatment Of Pah?mentioning
confidence: 99%